Exploring Arabic Teachers’ Motivational Strategies in Teaching Arabic in Indonesia - Toto Edidarmo; Alawiyah, N. Lalah; Rahim, Husni (UIN Syekh Wasil Kediri, Indonesia, 2025)
Abstract: This study describes and report effective motivational strategies used by Arabic language teachers in Indonesia to enhance students’ proficiency. A descriptive survey was conducted with 100 teachers from 11 provinces: Nanggroe Aceh Darussalam, North Sumatra, South Sumatra, Riau, Lampung, Banten, DKI Jakarta, West Java, Central Java, South Sulawesi, and North Maluku. Respondents were selected based on professional qualifications, with most having completed the Teacher Professional Education (PPG) program. Findings indicate that the most effective strategies include rewards and recognition, contextual approaches, modeling-based learning, the use of technology and interactive media, and providing challenges and opportunities for achievement. Teachers also emphasized the importance of creating a positive and supportive learning environment to strengthen student motivation. Analysis shows that 22% of respondents prioritized rewards such as gifts, points, or praise, while 20% highlighted the creation of a positive and interactive environment. About 18% stressed linking learning to real-life applications such as scholarships, careers, and religious practice. Meanwhile, 15% emphasized varied and innovative methods, including games, technology, Arabic clubs, and project-based learning. Personal and emotional approaches were considered important by 12%, while direct modeling of Arabic language use accounted for 8%, and student involvement in learning and assessment was noted by 5%. Overall, the study highlights that a combination of rewards, engaging environments, contextual relevance, and innovative teaching strategies significantly enhances both intrinsic and extrinsic motivation. These findings contribute to improving the quality of Arabic language teaching in Indonesia by aligning motivational strategies with students’ needs, learning contexts, and broader educational goals. Abstrak: Penelitian ini bertujuan menjelaskan dan melaporkan strategi motivasi yang efektif digunakan guru bahasa Arab di Indonesia untuk meningkatkan kemampuan berbahasa siswa. Metode penelitian adalah survei deskriptif dengan melibatkan 100 guru bahasa Arab dari 11 provinsi: Nanggroe Aceh Darussalam, Sumatera Utara, Sumatera Selatan, Riau, Lampung, Banten, DKI Jakarta, Jawa Barat, Jawa Tengah, Sulawesi Selatan, dan Maluku Utara. Responden dipilih berdasarkan kualifikasi profesional, mayoritas telah menyelesaikan Pendidikan Profesi Guru (PPG). Hasil penelitian menunjukkan strategi motivasi yang dianggap paling efektif meliputi penggunaan reward dan pengakuan, pendekatan kontekstual, pembelajaran berbasis pemodelan, pemanfaatan teknologi dan media interaktif, serta pemberian tantangan dan kesempatan berprestasi. Guru juga menekankan pentingnya menciptakan lingkungan belajar yang positif, menyenangkan, dan mendukung perkembangan motivasi siswa. Analisis data menunjukkan sebagian besar responden menekankan pemberian reward berupa hadiah, poin, atau pujian (22%) serta penciptaan lingkungan belajar positif dan interaktif (20%). Selain itu, 18% responden menilai penting mengaitkan pembelajaran dengan kehidupan nyata, manfaat, dan tujuan praktis seperti beasiswa, karier, maupun ibadah. Sebanyak 15% menekankan penggunaan metode variatif dan inovatif seperti permainan, teknologi, Arabic club, atau proyek. Pendekatan personal dan emosional mendapat perhatian 12% responden, sementara pemberian teladan praktik bahasa Arab langsung mencapai 8%, dan pelibatan siswa aktif dalam pembelajaran serta penilaian sebesar 5%. Temuan ini menegaskan bahwa kombinasi antara reward, lingkungan belajar yang menyenangkan, relevansi materi, serta metode inovatif dapat secara signifikan meningkatkan motivasi intrinsik dan ekstrinsik siswa dalam pembelajaran bahasa Arab.